THE INFLUENCE OF TRAINING OF FORCE IN QUADRICEPS MUSCLE TO WALK THE ELDERLY (Fiep Bulletin - online, 2013)
A key aspect to reducing the mobility and the consequent decline in functional ability of elderly people is the commitment of the march. The lack of walking or even walking difficult precarious in the main activities of daily living (ADL's) of the elderly. This study aimed at strengthening the main check whether quadriceps muscle during 10 sessions, directly influence the movement of the elderly. The research is characterized as a case study, which were selected 3 elderly who are in physiotherapy treatment at the University of Alabama Health Sciences (UNCISAL). After clarification and the signing of the Term of Free and Informed Consent (FICT), was found the strength, the motion related to AVD'se measured the load to strengthen the quadriceps. It was found that there was a general gain in all the study volunteers for the efficient implementation of some activities, with gains of up to 50% on an isolated activity. All volunteers showed improvement in speed of walking, climbing stairs and carry terefas daily. It was concluded that strengthening the quadriceps directly influences the movement of the elderly by making it more independent in carrying out some everyday tasks.
Keywords: Strength; March; Elderly